Life history mediates the association between parasite abundance and geographic features. Issue 5 (7th April 2022) - Williams, Maureen A.; Faiad, Sara; Claar, Danielle C.; French, Beverly; Leslie, Katie L.; Oven, Emily; Guerra, Ana Sofia; Micheli, Fiorenza; Zgliczynski, Brian J.; Haupt, Alison J.; Sandin, Stuart A.; Wood, Chelsea L.
Abstract: Although parasites are ubiquitous in marine ecosystems, predicting the abundance of parasites present within marine ecosystems has proven challenging due to the unknown effects of multiple interacting environmental gradients and stressors. Furthermore, parasites often are considered as a uniform group within ecosystems despite their significant diversity. We aim to determine the potential importance of multiple predictors of parasite abundance in coral reef ecosystems, including reef area, island area, human population density, chlorophyll‐ a, host diversity, coral cover, host abundance and island isolation. Using a model selection approach within a database of more than 1, 200 individual fish hosts and their parasites from 11 islands within the Pacific Line Islands archipelago, we reveal that geographic gradients, including island area and island isolation, emerged as the best predictors of parasite abundance. Life history moderated the relationship; parasites with complex life cycles increased in abundance with increasing island isolation, while parasites with direct life cycles decreased with increasing isolation. Direct life cycle parasites increased in abundance with increasing island area, although complex life cycle parasite abundance was not associated with island area. This novel analysis of a unique dataset indicates that parasite abundance in marine systems cannot be predicted precisely without accounting for the independent and interactive effects of each parasite's life history and environmental conditions. Abstract : Parasites that live in coral reef fishes can be abundant or rare. This work shows that geographic features, like island area and isolation, are most associated with the number of parasites in fish. The relationship between parasite abundance, and island isolation and area depends on whether parasites can be directly transmitted from host to host.